2017
DOI: 10.1016/j.mvr.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of cyclooxygenase in the vascular response to locally delivered acetylcholine in Caucasian and African descent individuals

Abstract: CAU have a greater endothelial reactivity than AFD in both foot and finger skin sites irrespective of COXib. It is concluded that the lower ACh-induced vasodilatation in AFD is not due to a compromised COX pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Average skin blood flow in response to iontophoresis of ACh was calculated over the final 20 seconds of the interval between successive pulses and between 40 to 60 seconds after the final pulse (Maley et al, 2017). These responses were expressed as absolute CVC as baseline CVC did not differ between conditions for any site.…”
Section: Measurementsmentioning
confidence: 99%
“…Average skin blood flow in response to iontophoresis of ACh was calculated over the final 20 seconds of the interval between successive pulses and between 40 to 60 seconds after the final pulse (Maley et al, 2017). These responses were expressed as absolute CVC as baseline CVC did not differ between conditions for any site.…”
Section: Measurementsmentioning
confidence: 99%
“…Using this new approach, we demonstrated that ethnicity per se does not influence NO-dependent cutaneous vasodilatation or sweating in healthy young men during rest, moderate-intensity exercise and recovery in dry heat. That said, differences in cutaneous vasodilator responsiveness between men of black-African and Caucasian descent have been observed in other experimental conditions Kim et al, 2018;Maley et al, 2017). This indicates that ethnicity should remain an important consideration when designing mechanistic studies to evaluate local thermoeffector control, depending on the modulator being investigated and the experimental conditions being used.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, black-African descendants demonstrate reduced forearm (Ozkor et al, 2014) c 2019 The Authors. Experimental Physiology c 2019 The Physiological Society and local cutaneous (Maley, House, Tipton, & Eglin, 2017) vasodilator responsiveness relative to Caucasians. Furthermore, sweat gland activation during passive heat exposure is lower in men of black-African descent than in Caucasians (Kawahata & Adams, 1961) albeit, relative increases in sweat output in response to phamacological stimulation have also been reported for men of black-African descent (Gibson & Shelley, 1948).…”
Section: Introductionmentioning
confidence: 99%
“…For a number of years, investigators conducting studies on human thermoregulatory function have often selected participants from only one ethnic group to minimize the confounding influence of ethnicity (Glickman-Weiss, Nelson, Hearon, & Day, 1997;Stephens & Hoag, 1981). This might remain an important consideration for more mechanistic research directed at the evaluation of thermoeffector control, especially given that there is evidence of ethnicity-related differences in the control of cutaneous blood flow (Maley, House, Tipton, & Eglin, 2017b, 2017a. However,…”
Section: Discussionmentioning
confidence: 99%